Produção de cultivares e híbridos F1 de repolho (Brassica oleracea var. capitata) na região serrana do estado do Rio de Janeiro - Rocha Leal , Nilton; Arume , Alfredo K (Revista Ceres, 2025)
This study was conducted at Santa Rosa, Teresópolis, state of Rio de Janeiro in 1970, with the purpose of testing the yield potential of cabbage (Brassica oleracea var. capitata) cultivars and F1 hybrids. The F1 hybrid soshe yielded best with 39,031 kg/ha and with a head mean weight of 1,870 g. The cultivar 'Copenhagen' was the poorest producer with 20,677 kg/ha and a head mean weight of 1,000 g. Best head formation was observed in the F1 hybrids 'Top Sango’ and 'Soshu' and the cultivar 'Copenhagen'.